The Effect of Leadership Style and Sustainable Work Environment on Employee Performance with Work Motivation as a Mediating Variable at the Directorate General of Chemical, Pharmaceutical, and Textile Industries, Ministry of Industry, Republic of Indonesia - Zainal, Muhammad; Aktif Budiono, Nur (Dinasti International Journal of Digital Business Management, 2025)
This study aims to determine the effect of leadership style, work environment, and work motivation on employee performance. The type of research approach that the author uses is quantitative as a scientific method because the data is concrete, objective, measurable, rational and systematic. The sample used in this study used a non-probability sample method with the sampling technique being purposive sampling and the population in this study were employees at the Directorate General of Chemical Pharmaceutical and Textile Industries, Ministry of Industry totaling 161 people and a sample of 112 respondents was obtained. Data processing techniques in this study used the help of Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that leadership style has a positive and significant effect on employee performance, work environment has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, leadership style has a positive and significant effect on employee work motivation, work environment has a positive and significant effect on employee work motivation, leadership style mediated by work motivation has a significant effect on employee performance, work environment mediated by work motivation has a significant effect on employee performance at the Directorate General of Pharmaceutical and Textile Chemical Industry, Ministry of Industry of the Republic of Indonesia.